(untitled) (Research, Society and Development, 2021)
This work intends to provoke reflection on the influence of proximal processes in the social development of children based on the bioecological theory of development. To develop the proposal, articles were selected that fit the theme. The study allowed us to understand that children suffer intense influences from proximal processes and that these are influenced by the person’s characteristics and the environment. Thus, proximal processes can be understood as the engine or driving force of child social development.